Potential of 14C-based versus ∆CO-based ∆ffCO2 observations to estimate urban fossil fuel CO2(ffCO2) emissions - Maier, Fabian; Rödenbeck, Christian; Levin, Ingeborg; Gerbig, Christoph; Gachkivskyi, Maksym; Hammer, Samuel (EGUsphere, 2023)
Abstract. Atmospheric transport inversions are a powerful tool for independently estimating surface CO2 fluxes from atmospheric CO2 concentration measurements. However, additional tracers are needed to separate the fossil fuel CO2 (ffCO2) emissions from natural CO2 fluxes. In this study we focus on radiocarbon (14C), the most direct tracer for ffCO2, and the continuously measured surrogate tracer carbon monoxide (CO), which is co-emitted with ffCO2 during incomplete combustion. In the companion paper by Maier et al. (2023a) we determined for the urban Heidelberg observation site in Southwestern Germany discrete 14C-based and continuous ∆CO-based estimates of the ffCO2 excess concentration (∆ffCO2) compared to a clean-air reference. Here, we use the CarboScope inversion framework adapted for the urban domain around Heidelberg to assess the potential of both types of ∆ffCO2 observations to investigate ffCO2 emissions and their seasonal cycle. We find that discrete 14C-based ∆ffCO2 observations from almost 100 afternoon flask samples collected in the two years 2019 and 2020 are not well suited for estimating robust ffCO2 emissions in the main footprint of this urban area with a very heterogeneous distribution of sources including several point sources. The benefit of the continuous ∆CO-based ∆ffCO2 estimates is that they can be averaged to reduce the impact of individual hours with an inadequate model performance. We show that the weekly averaged ∆CO-based ∆ffCO2 observations allow for a robust reconstruction of the seasonal cycle of the area source ffCO2 emissions from temporally flat a-priori emissions. In particular, the distinct COVID-19 signal with a steep drop in emissions in spring 2020 is clearly present in these data-driven a-posteriori results. Moreover, our top-down results show a shift in the seasonality of the area source ffCO2 emissions around Heidelberg in 2019 compared to the bottom-up estimates from TNO. This highlights the huge potential of ∆CO-based ∆ffCO2 to verify bottom-up ffCO2 emissions at urban stations if the ∆CO / ∆ffCO2 ratios can be determined without biases.